Species Inventory of Araceae In West Block of Batang Toru Forest, North Tapanuli Regency, North Sumatra - Nursahara Pasaribu (International Journal of Ecophysiology, 2021)
Araceae is a family plant that generally inhabits the tropical region with relatively high humidity such as The Batang Toru Forest Area. Environmental conditions such as humid or wet, watery, shady and high rainfall support the growth of Araceae species. Araceae have an unique spadix inflorescence characteristic that protected by spatha. A study on Araceae in Batang Toru Forest Area has never been conducted, leaving the unknown status of the species diversity and distribuion. The aims of this study was to invent Araceae in The Batang Toru Forest West Block area. The study was carried out from July to September 2018. The exploration method were used to invent the Araceae along the existing track path. There were 34 species of Araceae belonging to 8 genera found in the study side. All of species, 25 of them were lived as terrestrial and 9 of them were as epiphytes. The genera with the most species are Homalomena (12 species) and the least are Pothos (1 species). Araceae can lived on the soil, stones, trees, riparian and pond. Araceae can be found at various altitude with high air humidity (73-99 %) and warm temperature (17-27 °C). Araceae also like acid soil (4-7), warm (19-27 °C) with various humidity (1.5-8).